Halogen Enrichment of Siberian Traps Magmas During Interaction With Evaporites - Sibik, Svetlana; Edmonds, Marie; Villemant, Benoit; Svensen, Henrik H.; Polozov, Alexander G.; Planke, Sverre (Frontiers in Earth Science, 2021)
Volatile emissions to the atmosphere associated with the Siberian Traps eruptions at the Permian-Triassic boundary were sourced from the outgassing of primary magmas and the sedimentary host rocks into which they were intruded. Halogens in volcanic gases may have played an important role in environmental degradation and in stratospheric ozone destruction. Here we investigate how halogens behave during the interaction between salts and basalt magma emplaced as sills and erupted as lava. We present whole-rock, trace, and halogen concentrations for a suite of samples from three locations in the Siberian Traps Large Igneous Province, including basalt lavas erupted, and dolerites intruded into both organic-bearing shales and evaporites. Dolerites are enriched in Cl, Br, and I; their enrichment in Cl is similar to MORB and OIB that have been inferred to have assimilated seawater. The dolerites exhibit halogen compositional systematics, which extend towards both evaporites and crustal brines. Furthermore, all analyzed samples show enrichment in Rb/Nb; with the dolerites also showing enrichment in Cl/K similar to MORB and OIB that have been inferred to have assimilated seawater. We infer that samples from all three locations have assimilated fluids derived from evaporites, which are components of crustal sedimentary rocks. We show that up to 89% of the chlorine in the dolerites may have been assimilated as a consequence of the contact metamorphism of evaporites. We show, by thermal modeling, that halogen transfer may occur via assimilation of a brine phase derived from heating evaporites. Halogen assimilation from subcropping evaporites may be pervasive in the Siberian Traps Large Igneous Province and is expected to have enhanced emissions of Cl and Br into the atmosphere from both intrusive and extrusive magmatism.